Pengaruh Infrared dan William Flexion terhadap Skala Nyeri Low Back Pain Myogenik pada Pembatik - Vira Khoirul Nissa; Fiqi Widyawati; Azizah Rahmawati; Young Ari Kusworo (LPPM Institut Pendidikan Nusantara Global, 2026)
Myogenic Low Back Pain (LBP) is a musculoskeletal disorder commonly experienced by batik workers due to prolonged static postures and repetitive movements, resulting in pain and functional limitations. Infrared, as a superficial heat therapy modality, and William Flexion exercises are physiotherapy interventions used to reduce pain associated with myogenic LBP. This study aimed to evaluate the effects of Infrared and William Flexion on pain intensity among batik workers with myogenic Low Back Pain and to compare the effectiveness of both interventions. A quantitative study with a quasi-experimental two-group pre-test–post-test design was conducted involving 40 batik workers selected through purposive sampling and allocated into two intervention groups. Pain intensity was assessed using the Visual Analog Scale (VAS) and analyzed using paired sample t-tests and an independent sample t-test. The Infrared group showed a significant reduction in mean pain scores from 6.53 to 4.58 (p < 0.001; Cohen's d = 3.94), while the William Flexion group demonstrated a significant decrease from 6.72 to 4.76 (p < 0.001; Cohen's d = 2.67), indicating very large clinical effects in both groups. However, no significant difference was found between the two interventions (p = 0.573). It can be concluded that both Infrared therapy and William Flexion exercises are equally effective in reducing pain among batik workers with myogenic Low Back Pain, with both interventions demonstrating substantial clinical benefits.